Effect of educational intervention on the appropriate use of oral antimicrobials in oral and maxillofacial surgery: a retrospective secondary data analysis - Junya Kusumoto; Atsushi Uda; Takeshi Kimura; Shungo Furudoi; Ryosuke Yoshii; Megumi Matsumura; Takayuki Miyara; Masaya Akashi (BMC, 2021)
Abstract Background In Japan, oral third-generation cephalosporins with broad-spectrum activity are commonly prescribed in the practices of dentistry and oral surgery. However, there are few reports on the appropriate use of antibiotics in the field of oral surgery. This study aimed to evaluate the appropriateness of antibiotic use before and after an educational intervention in the Department of Oral and Maxillofacial Surgery, Kobe University Hospital. Methods The use of oral antibiotics was investigated among inpatients and outpatients before and after an educational intervention conducted by the antimicrobial stewardship team. Additionally, the frequency of surgical site infection after the surgical removal of an impacted third mandibular molar under general anesthesia and the prevalence of adverse effects of the prescribed antibiotics were comparatively evaluated between 2013 and 2018. Results After the educational intervention, a remarkable reduction was noted in the prescription of oral third-generation cephalosporins, but increased use of penicillins was noted among outpatients. There was reduced use of macrolides and quinolones in outpatients. Although a similar trend was seen for inpatients, the use of quinolones increased in this population. Despite the change in the pattern of antibiotic prescription, inpatients who underwent mandibular third molar extraction between 2013 and 2018 did not show a significant increase in the prevalence of surgical site infections (6.2% vs. 1.8%, p = .336) and adverse effects of drugs (2.1% vs. 0%, p = .466). Conclusions This study suggests that the judicious use of oral antibiotics is possible through conscious and habitual practice of appropriate antibiotic use. However, further investigation is required to develop measures for appropriate use of oral antibiotics.